An ethnographic study of schizophrenia in Zimbabwe: The role of culture, faith, and religion - Chidarikire, Sherphard (Journal of spirituality in mental health, 2020)
This ethnographic study explored the experiences of eighteen Shona speakers living with schizophrenia in Zimbabwe. Data were collected using semistructured interviews, observations and field notes. Almost three in four participants reported having a strong religious affiliation and believed mental illnesses are caused by spirits (zvirwere zvemweya) or witchcraft (zvirwere zvevaroyi). Cultural and religious beliefs influenced the perceived causes of schizophrenia, symptom explanations, and help-seeking behavior. Schizophrenia compounded social disadvantage, often leading to family disruption, isolation, homelessness, and wandering. Faith and religious belonging provided participants access to support and fostered hope, resilience, a sense of self-worth and greater quality of life.